Area-wide pest management and prospects for fall armyworm control on smallholder farms in Africa: A review - Kansiime K. Monica; Makale Fernadis; Chacha Duncan; Nunda Winnie; Karanja Daniel; Durocher-Granger Léna (Sustainable Environment)
Currently, the management of many highly mobile and very destructive insect pests such as fall armyworm is still carried out for the most part, on a field-by-field basis. Chemical pesticides remain the most predominant pest control option, despite their direct effects on human health, the environment, and biodiversity. Integrated Pest Management which involves the use of a combination of techniques has been promoted for the long-term prevention of pests, but they too, are usually applied by producers independently of others. Uncoordinated and reactive field-by-field pest management addresses only a small fraction of a local pest population, allowing for fast re-invasion of managed farms. Area-wide pest management, where coordinated pest management tactics are used over a broad landscape, has been suggested as a key strategy for the sustainable management of invasive and mobile pests. Using narrative review methodology, we give a description and synthesis of available literature on area-wide pest management on smallholder farms around the world. We specifically examine the successes, facilitators, and barriers to effective implementation of the approach. We discuss these cases considering changing institutional and socio-economic factors and assess prospects for sustainable area-wide management of fall armyworm in Africa.